New Kinds of Blocking sets in a Projective Plane PG(2,q) - Mahammad, A.T.; Mahammad, M. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, new kinds of blocking sets in a projective plane over Galois field PG(2,q) can be obtained. These kinds are called the complete blocking set and maximum blocking set. Some results can be obtained about them.